In the Russian Press (Niva Magazine) Evaluations on the Second Constitutional Process - Celik, Ahmet (Ege Univ, 2020)
The declaration of the Second Constitutional Era, which was a turning point for the political and social structure of the Ottoman State, was an important event affecting the internal and external conjuncture of the period. The process that brought the turmoil in Ottoman domestic politics, led to the revision of the great powers in foreign policy to the policies of the Ottoman State. In this process, Russia, which pursued a policy on both the Straits and the Slavs in the Balkans, was closely interested in this process due to the influence of Germany on the Ottoman Empire. The Russian press organ Niva Magazine, which published in this process, included the news through the Constitutional Period and made comments and evaluations. In our study; the news and evaluations of the Niva Magazine, which publishes on a weekly basis, about the Second Constitutionalist period were examined and the purpose of these evaluations were compared with the written literature related to the process.
Keywords: Second Constitutional Monarchy; Russian Press; Abdulhamit II; March 31 Revolt